1999
DOI: 10.2202/1949-6605.1077
|View full text |Cite
|
Sign up to set email alerts
|

Fairness, Educational Value, and Moral Development in the Student Disciplinary Process

Abstract: This study examines the relationship between college students' percqtions of the fairness and educatiwlvalue of the disciplinary process and their moral development. Participants woe unde~graduate students charged with mino~disciplinary violations. The research sample displayed lower levels of moral development than normative Defining Issues Test samples of unde~paduates. Additionally, the highe~the students' lwels of moral development, the more likely they perceived the process as having educational value, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Boots (1987) argued that part of the judicial professional's role was assisting students to learn and grow from their judicial experience. Mullane (1999) examined the relationship between college students' perceptions of the fairness and educational value of campus judicial systems and their own moral development. The results of the study suggested that college students involved in judicial systems exhibited lower levels of moral development than typical students in the normative samples used in the study (Mullane, 1999).…”
Section: Judicial Programs and Services In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Boots (1987) argued that part of the judicial professional's role was assisting students to learn and grow from their judicial experience. Mullane (1999) examined the relationship between college students' perceptions of the fairness and educational value of campus judicial systems and their own moral development. The results of the study suggested that college students involved in judicial systems exhibited lower levels of moral development than typical students in the normative samples used in the study (Mullane, 1999).…”
Section: Judicial Programs and Services In Higher Educationmentioning
confidence: 99%
“…Mullane (1999) examined the relationship between college students' perceptions of the fairness and educational value of campus judicial systems and their own moral development. The results of the study suggested that college students involved in judicial systems exhibited lower levels of moral development than typical students in the normative samples used in the study (Mullane, 1999). It was suggested that practitioners could provide opportunities for moral development as a way of lessening the likelihood of student misconduct (Mullane, 1999).…”
Section: Judicial Programs and Services In Higher Educationmentioning
confidence: 99%